Influence of pine resin on thermo-mechanical properties of pumice-cement composites - Bicer, Ayse; Celik, Nevin (Elsevier Sci Ltd, 2020)
In this study, aggregate pumices are used to produce new construction materials with low density. Pumices are grinded and then classified according to their maximum grain diameter, namely d(max) <= 5 mm, d(max) <= 10 mm and d(max) <= 20 mm. The cement is added into each group as the binder material. The pumice ratios in the specimens are estimated to be 20, 40, 60 and 80% of the total volume. Moreover, pine resin (approximately 1% of cement + pumice mixture) is added to concrete grout to generate artificial pores in each specimen group. The prepared samples are dried during 28 days at room temperature and then the thermo-mechanical measurements are carried out. It was observed that, as the pumice ratio and particle diameter increase, the porosity and water absorption increase, but density, thermal conductivity and compressive strength decrease. Some artificial pores (in addition to pumice pores) are generated in concrete blocks, leading to improvement of insulation properties of the material. The thermal concutivity respectively decreases as 8-15%, 7-12% and 5-13% for the resin-mixed samples with d(max) <= 5 mm, d(max) <= 10 mm and d(max )<= 20 mm. Similarly, the compressive strength values drop 10-13%, 6-10% and 8-12% respectively for each dimeter group.
Keywords: Pumice; Pine resin; Aggregates; Light concrete